2008
DOI: 10.1159/000111740
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Hypospadiac Urethral Duplication with Dismembered Urethroplasty

Abstract: Urethral duplication is a complex and rarely seen anomaly with three anatomic variants: epispadiac (dorsal), hypospadiac (ventral) and Y-type. Here we report an 11-year-old male patient with hypospadiac urethral duplication who presented with daytime urinary incontinence and dribbling, urethral stricture and possible obstructive uropathy. After endoscopic treatment of the stricture in the ventral (dominant) urethra, urethral reconstruction was done anastomosing the ventral (dominant) and dorsal (non-dominant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…2 There have been cases reported that are associated with a single hypospadic urethra, commonly associated to an atretic accessory channel distally, such as in type 1A lesions. 9,10 The type 2 A-II group is characterized by the presence of a second urethra which divides from the main urethra, and maintains a separate course. This group includes a subgroup of patients in whom the ventral urethra opens in the perineum ("Y-type" duplication) (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 There have been cases reported that are associated with a single hypospadic urethra, commonly associated to an atretic accessory channel distally, such as in type 1A lesions. 9,10 The type 2 A-II group is characterized by the presence of a second urethra which divides from the main urethra, and maintains a separate course. This group includes a subgroup of patients in whom the ventral urethra opens in the perineum ("Y-type" duplication) (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are three anatomic variants of urethral duplication: epispadiac (dorsal), hypospadiac (ventral), and Y-type. [9] However, according to the Effmann's classification,[2] there are three types. Type I is a blind incomplete urethral duplication.…”
Section: Discussionmentioning
confidence: 99%
“…Duplication of urethra presents with three anatomic variants: epispadiac (dorsal), hypospadiac (ventral) and Y-type [2]. Most duplications lie in the same sagittal plane one above the other.…”
Section: Discussionmentioning
confidence: 99%